A SHORT CRITICISM OF HEIDEGGER'S ONTOLOGICAL ANALYSIS OF THE TERM “BEING” - B. Bratina (Vestnik MGIMO-Universiteta)
The text scrutinizes Heidegger's attempt of ontological analysis of three linguistical roots of the term “being” (es-, bhu-, wes-) from The Freiburg lectures (1935). In author's opinion, Heidegger deliberately ignored the presence of the roots and their modifications in the Slavic languages. Notional and even ideological reasons of such «inattention» are pressumed, the reasons which determine linguistic conclusions of German philosopher (and not the other way around, as supposed when stated that linguistic bacame an absolutely independent scientific means of Heidegger's ontological «investigations»).At the same time, the author argues for an independent ontological and linguistic analysis of Slavic languages, to fill the philogophical «gapes», originated from ignoring the rich semantic content of those languages. The linguistic richness of Slavic radices is one of so far loosely developped means of knowing the important philosophical notions, including the notion «being». Turning the attention towards ethimological components of ontological and linguistical analysis is, of course, one of Heidegger's merits. But the different perspectives of that endevour, which show up in research of Slavic culture's material, radically change the practical concequences of those theses in the cultural and political plane. On the whole, they prevent the insight into aspirations of some contemporary political powers in marginalizing the Slavic cultures, ignoring their real position in global comunity, as well as the contributon of the Slavic cultures to the tresury of world cultures.The most important conclusion of the article is stressing of necessity to consider political conditionalities (residua) in philosophical positions, which the authors themselves are often unaware of. Calling to intellectual consciousness, Boris Bratina convincingly substantiates the methodological and research of content that follows from given positions.